The Addiction-Troop Test Theoretical Considerations and Procedural Recommendations. [article]. - Cox, W. Miles
Decisions about using addictive substances are influenced by addiction-related stimuli, of which the user might be unaware. The addiction-Stroop task is a paradigm used to assess this distruction. The empirical evidence for the addiction-stroop is critically reviewed, and a meta-analyses of alcohol-related and smoking-related studies are presented. Studies finding the strongest effects were those in which participants had strong current concerns about an addictive substance or such concerns were highlighted through experimental manipulations, especially those depriving participants of the substance. Theories to account for addiction-related attentional bias are discussed, of which the motivational theory of current concerns appears to provide the most complete account of the phenomenon. Recommendations are made for maximizing the precision of the addiction-Stroop test in the future research. -- (from the author)